TIPE KEPEMIMPINAN PONDOK PESANTREN HASAN JUFRI DESA LEBAK KECAMATAN SANGKAPURA KABUPATEN GRESIK - Maulidal Mustofa (STAI Ma'had Aly Al-Hikam Malang, 2022)
This study aims to find out and obtain information about the type of leadership at the Hasan Jufri Islamic Boarding School. This study uses a qualitative approach. Research data obtained from various sources using information gathering techniques, data through observation and interviews there are several people who the researchers interviewed first: boarding school caregivers, senior students. deliberation process; secondly, the communication between the leader of the Islamic boarding school is carried out with superiors and subordinates along with alumni as well as subordinates and alumni, with superiors communicating; The third supervision carried out by the leader of the Hasan Jufri Islamic Boarding School towards his subordinates aims to get a solution. In general, it can be concluded that the success achieved by the leader of the Hasan Jufri Islamic Boarding School is increasing and the leadership type of the Hasan Jufri Islamic Boarding School is categorized as democratic leadership.